SYMBOLIC MEANINGS of MANUK RULU in KARONESE MARRIAGE TRADITION - Efendi Barus; Emmy Erwina; Susi Ekalestari; Risnawaty (PT Inovasi Pratama Internasional, 2023)
Semiotics thus includes different resources, such as language, images, music, sound and embodied action, and the meanings which arise as choices from these resources combine in semiotic phenomena such as texts, interactions and events (KAY L O’HALLORAN: 2020). This research is concerned with the symbolic meaning of Manuk Rulu in Karonese Marriage Tradition. Manuk Rulu is a tradition or culture in Karo people usually presented by the couple of marriage and the groom’s parents to Kalimbubu. It indicates the respect given to Kalimbubu in the hope that through the pray of them to the Almighty God, the marriage couple can get harmonious, happy, peaceful life and getting descendant, son and daughter. The aim of this research is to find and elaborate the symbolic meaning of Manuk Rulu in Karo tradition. This tradition is found in Deli Serdang Region. Manuk Rulu consists of: Manuk Raja Mulia “the symbol of Respectfulness, Loyalty, Obedience to Kalimbubu so that through this tribute hopingly the marriage couple can get blessing from God. The result of this research can be shown here such as those symbolic meanings are found here such such bravery in facing the life, sincere heart, quality or glory of speech. The method of research is done by descriptive qualitative research proposed by Hancock (1998). The main theory to support this research is the theory of Semiotics by Charles Sanders Pierce (1990). This research can be concluded that the local tradition of Karo people can reflect the Semiotic Symbols which are considered valuable to the language learners.